Is there any regional price disparity in Peninsular Malaysia? - Lee, Chin (Cluj University Press, 2015)
This study examines whether there are significant differences in prices across four regions in Peninsular Malaysia, namely Northern, Central, Southern, and Eastern Peninsular Malaysia. Disaggregate monthly consumer price indices for twelve types of goods and services from July 2010 to February 2013 were analyzed. Based on the Levin and Lin (1993) panel unit root test, this study found statistical evidence of price convergence among the four zones for two-thirds of the price groups. Most importantly, price convergence exists for three major consumers' expenditures items: Food and Non-Alcoholic Beverages; Housing, Water, Electricity, Gas and Other Fuels; and Transport. Indeed, these eight price groups that converged comprised 83.6% of total consumer expenditures. Evidence of price convergence among these price groups suggests that Peninsular Malaysia markets are highly integrated. In addition, this study found that the half-life for the tradable goods is roughly 2-3 months and for nontradable goods about 5-10 months. These findings indicate that tradable goods prices adjust more rapidly than nontradable goods do.